Interactive 3D Driving Test Simulation (13DDTS) / Syahizad Zuriatie Mohamad Zuki - Syahizad Zuriatie , Mohamad Zuki (2004)
Interactive 3D Driving Test Simulation is a project develops a virtual world of interactive 3D with simulation. There are some major features associated with the system. This project system is not only provides better services for the user but also helps immensely to the driving school internal management. The purpose of this project was to identify innovative and feasible applications of existing simulation and other electronic device technology with clear potential for the safety training of novice drivers and professional users through an effective lesson using this courseware. This Interactive 3D Driving Test Simulation project is divided into two main parts which is to create the model of the component that is included in the driving test and integrate all the models to form a fully function system. The model that are included in this Interactive 30 Driving Test Simulation are the driving test environment itself such as the road, housing, roundabout, traffic light and so forth. The most important model is the vehicle that is use by the user in the 30 driving test. The tools that are going to be used to develop the model for these projects are three dimensional software. The engine development is the major part to integrate the entire model to form a fully function system. A driving test simulation is a virtual reality tool that makes the driver feels like driving in a real car. A driver simulator normally consists of several subsystems such as real-time vehicle dynamics simulation, motion and force feedback, virtual reality system, rendering graphic and transferring the simulation data and more.